Post-keynésiens et régulationnistes :Une alternative à la crise de l’économie standard ? - Robert Boyer (Revue de la Régulation)
The two research programs, post-Keynesian and régulationist, have in common to provide an alternative to standard economics whose inability to account for the stylized facts observed since the 1970s, and even more in the current crisis, is now clear. A possible convergence was manifested first in the formalization of the Post War II Fordist growth regime as a particular form of cumulative causation, second in the analysis of successive speculative booms in terms of financial instability “à la Minsky” and finally by the use of stock-flow models in order to identify the transmission channels of monetary policy and check the sustainability of the ongoing disequilibria observed in the world economy and the European Union. These convergences are too few. This can be explained firstly by the reference of régulationists is more Marxist and Kaleckian than Keynesian but also by different epistemological stances: the search for a grand and universal theory by post-Keynesian versus analyzes historically and spatially situated for régulationists. The depth of the crisis in standard economic implicit epistemology, in its founding concepts and methods, opens a space for a joint research agenda between post-Keynesians and régulationists. The article offers four avenues. All should recognise the role of institutions and not just of economic policy in offsetting market failures. It could be fruitful to systematically review the empirical relevance of the various classes of models and not only their theoretical coherence. It is necessary to extend typically Keynesian mechanisms in order to reflect the multiple interdependencies found in contemporary economies. Finally, it is crucial to associate to any long-term growth model the forces and factors that may destabilize it, according to a process of endometabolism, typical of any capitalist economy. The current professionalization promoted by academic institutions is perhaps the main obstacle to the implementation of this promising research.